On the Shear-Deformation Theories for the Analysis of Concrete Shells Reinforced with External Composite Laminates - Ferreira, A. J. M. (Проблемы прочности, 2003)
A third-order theory of shear deformation is
used for description o a stress-strain state of
concrete shells reinforced with external composite
laminates. Reinforced concrete structures
play a key role in civil engineering. Corrosion
of steel re-bars is currently urgent, this problem
complicated due to porosity of concrete. To get
an adequate solution of the problem of strengthening
and retrofitting of degraded structures, external
composites bonded to the faces of
concrete structures are widely used. Deformation
of such kind of structures is highly nonlinear.
For the development of nonlinear
geometric and material models, we resort to the
numerical methods, in particular, to a finite-element
method. In the analysis of composite laminates,
high-order shear deformations are more
and more required. The proposed theory is an alternative
to the first-order one developed by
Ferreira et. al. earlier. The theory has been
approbated on a shell element which structure
represents a layered discretization of laminate
materials. For modeling of the deformation of
concrete in compression, perfectly plastic behavior
and strain-hardening plasticity o f the material
have been considered. We have discussed
a dual criterion of yielding and fracture of the
material in terms of stresses and strains which
is supplemented with a broken-line representation
of tension deformation curve, the horizontal
portion of this line corresponding to the
beginning of yielding. The behavior of unidirectional
composites is linear-elastic (brittle). Finite-
element analysis of a stress-strain state of a
concrete bar reinforced with composite strips
has been performed for three-point bending.
The observable reinforcement effects are described,
results of the application of the third-order
theory and comparative analysis of the
reinforcement of a concrete structure with composite
strips and the steel are given. Предложена теория сдвиговой деформации третьего порядка для описания напряженно-
деформированного состояния бетонных оболочек, армированных внешними композитными
ламинатами. Армированные бетонные конструкции - главные компоненты в строительной
отрасли. Коррозия стальных балок, используемых для армирования железобетонных конструкций,
является очень актуальной проблемой, которая усугубляется за счет пористости
бетона. В качестве адекватного решения проблемы упрочнения и модификации ослабленных
конструкций практикуется использование внешних композитных ламинатов, которые закрепляются
на наружных поверхностях бетонных конструкций. Деформирование такого
рода конструкций характеризуется значительной нелинейностью. Для разработки нелинейных
геометрических моделей и моделей материала используются численные методы, в
частности метод конечных элементов. Для анализа композитных ламинатов все чаще
используются сдвиговые деформации высокого порядка. Предлагаемая теория является
альтернативой теории первого порядка, ранее предложенной Феррейра с соавторами.
Теория опробована на элементе оболочки, структура которого позволяет воспроизвести
послойную дискретизацию ламинатных материалов. Для моделирования деформирования
бетона при сжатии использовались подходы идеально пластического и пластически-упроч-
няемого поведения материала. Рассмотрен двойственный критерий течения и разрушения
материала с точки зрения напряжений и деформаций, который применяется в сочетании с
представлением деформационной кривой при растяжении в виде ломаной линии с горизонтальным
участком, соответствующим началу пластического течения. Однонаправленные
композитные полосы характеризуются линейно-упругим (хрупким) поведением. Выполнен
конечно-элементный расчет напряженно-деформированного состояния армированной композитными
полосами бетонной балки, подвергнутой трехточечному изгибу. Описаны наблюдаемые
эффекты армирования, результаты применения теории третьего порядка и дан
сравнительный анализ упрочнения бетонной конструкции композитными полосами и стальной
арматурой. Запропоновано теорію зсувної деформації третього порядку для опису на-
пружено-деформованого стану армованих зовнішніми композитними ламінатами
бетонних оболонок. Армовані бетонні конструкції - головні компоненти
в галузі будівництва. Корозія стальних балок, що використовуються
для армування залізобетонних конструкцій, - дуже актуальна проблема, яка
посилюється за рахунок пористості бетону. Адекватним вирішенням
проблеми зміцнення і модифікації ослаблених конструкцій є використання
зовнішніх композитних ламінатів, котрі закріпляються на зовнішніх поверхнях
бетонних конструкцій. Деформування такого роду конструкцій характеризується
значною нелінійністю. Для розробки нелінійних геометричних
моделей та моделей матеріалу використовуються числові методи, зокрема
метод скінченних елементів. Для аналізу композитних ламінатів часто використовують
зсувні деформації високого порядку. Запропонована теорія є
альтернативою теорії першого порядку, яку запропонував раніше Феррейра
зі співавторами. Теорія опробована при розрахунку елемента оболонки,
структура якого дозволяє відтворити пошарову дискретизацію ламінатних
матеріалів. Для моделювання деформування бетону при стиску використовувалися
підходи ідеально пластичної та пластично-зміцнюваної поведінки
матеріалу. Розглянуто двоїстий критерій текучості і руйнування матеріалу
з точки зору напружень та деформацій, який використовується в
поєднанні з представленням деформаційної кривої при розтязі у вигляді
ломаної лінії з горизонтальною ділянкою, що відповідає початку пластичної
текучості. Односпрямовані композитні смуги характеризуються лінійно-
пружною (крихкою) поведінкою. Виконано скінченноелементний розрахунок
напружено-деформованого стану армованої композитними смугами бетонної
балки, яку піддавали триточковому згину. Описано спостережувані
ефекти армування, результати використання теорії третього порядку і проведено
порівняльний аналіз зміцнення бетонної конструкції композитними
смугами і стальною арматурою.